SUPERVALLEY: Reimagining Regenerative Landscapes and Circular Practices in a Transition Project - LaFleur, Filippo (Journal of Delta Urbanism, 2026)
This article explores the transformative potential of depleted agrarian spaces as catalysts for ecological transitions within post-metropolitan regions. Drawing on doctoral research in the Po River Valley mega-region of Northern Italy, the investigation examines how agricultural territories experiencing soil depletion can be reconceptualized through agro-ecological planning and design frameworks. The research positions soil regeneration as a foundational strategy within an ecology of repair, establishing degraded agrarian spaces as critical sites for intervention in future urban-rural systems. Through a multiscalar research-by-design methodology grounded in 25-hectare landscape units, the paper presents the "Super Valley" project: a spatial investigation for transforming depleted agricultural land into multifunctional regenerative landscapes that simultaneously restore ecosystem functions, maintain cultivation productivity, and generate diverse bio-based circular economies. The project explores how exhausted landscapes might become foundations for new ecologies-economies by regenerating carbon, water, and nutrient cycles. The innovation lies in integrating spatial design with urban-rural metabolic analysis to reimagine circular resource flows for regenerative territorial processes. The findings suggest pathways through which an ecology of repair applied to degraded agrarian spaces could transform sites of extraction into foundations for territorial regeneration, while acknowledging significant implementation challenges related to governance, economics, and social acceptance.